2022
DOI: 10.3390/ijms23031724
|View full text |Cite
|
Sign up to set email alerts
|

GFP–Margatoxin, a Genetically Encoded Fluorescent Ligand to Probe Affinity of Kv1.3 Channel Blockers

Abstract: Peptide pore blockers and their fluorescent derivatives are useful molecular probes to study the structure and functions of the voltage-gated potassium Kv1.3 channel, which is considered as a pharmacological target in the treatment of autoimmune and neurological disorders. We present Kv1.3 fluorescent ligand, GFP–MgTx, constructed on the basis of green fluorescent protein (GFP) and margatoxin (MgTx), the peptide, which is widely used in physiological studies of Kv1.3. Expression of the fluorescent ligand in E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Data on the properties of AgTx2-GFP and previously studied FP-Txs [ 7 , 45 , 46 , 47 ] have shown that FP-Txs can be considered as a reliable alternative to peptide blockers labeled with organic fluorophores for the fluorescent imaging of K v 1 channels, as well as for a number of analytical applications. FPs can modulate the pharmacological profiles of peptide blockers of K v 1 channels, maintaining a high (nanomolar) affinity to some of the target channels or even enhancing considerably the ligand selectivity for a particular channel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on the properties of AgTx2-GFP and previously studied FP-Txs [ 7 , 45 , 46 , 47 ] have shown that FP-Txs can be considered as a reliable alternative to peptide blockers labeled with organic fluorophores for the fluorescent imaging of K v 1 channels, as well as for a number of analytical applications. FPs can modulate the pharmacological profiles of peptide blockers of K v 1 channels, maintaining a high (nanomolar) affinity to some of the target channels or even enhancing considerably the ligand selectivity for a particular channel.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative strategy to create fluorescently labeled peptide blockers is the production of genetically encoded peptide toxins fused with fluorescent proteins (FPs) [ 7 , 45 , 46 , 47 ]. Currently, FPs used for such constructions are limited to TagRFP (hereinafter RFP) [ 48 ] and enhanced GFP [ 49 ], while a list of peptide blockers includes MgTx, OSK1, hongotoxin 1, and AgTx2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using GFP-MgTx, it became possible to identify peptide pore blockers and evaluate their affinity for the Kv1.3 channel. As potential drug candidates, GFP-MgTx can be utilized in screening and as a pre-selection tool for potassium channel blockers (70). Another conjugated form of MgTx with luminescent quantum dots (QDs), known as QD-MgTx, was utilized to assess its potency to block Shaker channels Kv1.1 to Kv1.7 using patch-clamp electrophysiology in HEK293 cells.…”
Section: Margatoxinmentioning
confidence: 99%
“…ShK-F6CA displays picomolar activity against K V 1.3 (IC 50 ∼ 48 pM) and >80-fold selectivity over K V 1.1 and K V 1.5. Other K V 1.3-blocking peptide toxins, such as MgTx, AgTx2, and OSK1, have been linked recombinantly to various FPs; the resulting fusions typically have modest (nM) affinities and K V 1.3 selectivity. …”
Section: Introductionmentioning
confidence: 99%